A study of domestic pigs, wilds suids and ticks as reservoirs for African swine fever virus in Uganda - Bjornheden, L. (Swedish University of Agricultural Sciences, 2011)
As the world’s population increases the need for food and good protein sources grows, especially in development countries like Uganda. The pig production is growing rapidly in Uganda and is not only a source of food but also an important income for many people living in the rural areas.African Swine Fever (ASF) is a contagious viral disease, which can cause up to 100% mortality among domestic pigs. This disease is endemic in Uganda and causes major economical and personal losses for farmers whom it affects directly or indirectly. Outbreaks occur every now and then, and in most cases the source of the infection is unknown. To better understand the dynamics of the disease, and sources of new infections, the aims of this study were to study different possible reservoirs for ASF (domestic pigs, wild suids and Ornithodoros ticks), and also to estimate the prevalence in one district, Rakai, in Southern Uganda, where pig production is an important source of income for the rural community. Another aim was to investigate the spatial behavior of a small number of bushpigs, to understand the interaction between these wild suids and their domestic relatives. Do they ever get in contact and thereby have the possibility to transfer ASFV from one another?DNA from African swine fever virus (ASFV) was found by PCR in nine of 239 domestic pigs with no clinical signs and in three out of four sampled soft ticks (Ornithodoros porcinus). Antibodies against ASFV were found in two of four sampled bushpigs, the only warthog sampled in the study and in five of the 239 domestic pigs, using a commercially available ELISA. Three of the PCR positive pigs were borderline cases on the ELISA. GPS readings of the movement of the bushpigs indicated possible interface with the domestic pigs.Conclusions made from this study are that domestic pigs, bushpigs, warthogs and soft ticks can act as reservoirs for ASFV. Domestic pigs and bushpigs can interact. The prevalence of ASFV in Rakai was 3.3% while the seroprevalence was 2.1%. The most important finding was the subclinical, ASFV positive pigs.